Efektivitas Implementasi Pendekatan Scientific dengan Model Problem Based Learning dan Learning Cycle 5E - Trysa Gustya Manda; Marsigit Marsigit (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
The purposes of this research are to describe and compare the effectiveness of the imple mentation of scientific approach using problem based learning and learning cycle 5E model viewed from achievement spiritual attitudes, social attitudes, knowledge, and skills of students on polyhedral topic in Junior High School Grade VIII. This research is quasi experiment using nonequivalent (pre-test and post-test) group design. Population in this research are all of students grade VIII Junior High School 12 Padang. The sample was grade VIII4 and VIII5. The instruments used are questionnaires spiritual attitude and social attitude, knowledge and skill test. The results of the research are as follows the implementation of scientific approach with problem based learning and learning cycle 5E model is effective viewed from the achievement spiritual attitudes, social attitudes and knowledge of students, but not effective viewed from students skill, and there are no differences between the effectiveness of the implementation of scientific approach using problem based learning and learning cycle 5E model.